Diversity of Cactaceae in the Flora of Bajío and adjacent regions (Mexico) - Aquino, David; Sánchez, Daniel; Arias, Salvador (Botanical sciences, 2025)
Background: Recent floristic lists indicate that the Mexican Bajío is a diverse area in terms of the number of species and endemism of Cactaceae. Questions and/or Hypotheses: 1) How many taxa are distributed in the Bajío and adjacent regions? 2) What are the vegetation types and biogeographic provinces with the greatest species richness? 3) What are the areas with the highest level of endemism? Studied species: Cactaceae family. Study site and dates: Bajío region (Guanajuato, Querétaro and northern part of Michoacán), México, which was visited between 2014 and 2022. Methods: With the use of herbarium, field collections and iNaturalist/iNaturalistMX records, a database was constructed from which species richness, weighted endemism and weighted endemism corrected by one-third degree cells were estimated. Results: Thirty genera and 125 species of cacti are reported. Xerophilous scrub is the type of vegetation that hosts the greatest number of species. The Chihuahuan Desert is the province with the highest level of richness. The cells with the highest richness and weighted endemism are found between the provinces of the Chihuahuan Desert and the Sierra Madre Oriental. In contrast, there is a decrease toward the Trans-Mexican Volcanic Belt. Conclusions: Of the three biogeographic provinces that converge in the Bajío region —the Trans-Mexican Volcanic Belt, the Chihuahuan Desert, and the Sierra Madre Oriental— the largest number of endemic species is found on the borders between the latter two, likely because this region was a climatic refuge during the Pleistocene. Antecedentes: Trabajos florísticos recientes indican que el Bajío mexicano es una zona diversa en número de especies y endemismos de Cactaceae. Pregunta y/o Hipótesis: ¿Cuántos taxones se distribuyen en el Bajío y regiones adyacentes? 2) ¿Cuáles son los tipos de vegetación y provincias biogeográficas con mayor riqueza de especies? 3) ¿Cuáles son las áreas con mayor nivel de endemismos? Especie de estudio: Familia Cactaceae. Sitio y fechas de estudio: Región del Bajío (Guanajuato, Querétaro y porción septentrional de Michoacán) México, visitada entre 2014 y 2022. Métodos: Con registros de herbario, colectas en campo y observaciones en iNaturalist/iNaturalistMX se construyó una base de datos a partir de la cual se estimó la riqueza de especies, el endemismo ponderado y el endemismo ponderado corregido por celdas de un tercio de grado. Resultados: Se reportan 30 géneros y 125 especies de cactáceas. El matorral xerófilo alberga la mayor cantidad de especies. El Desierto Chihuahuense resultó la provincia con mayor nivel de riqueza. Las celdas con mayor riqueza y endemismo ponderado se encuentran en los límites entre las provincias del Desierto Chihuahuense y la Sierra Madre Oriental. En contraparte, hay un descenso hacia la Faja Volcánica Transmexicana. Conclusiones: De las tres provincias biogeográficas que convergen en la región del Bajío —la Faja Volcánica Transmexicana, el Desierto Chihuahuense y la Sierra Madre Oriental— el mayor número de especies endémicas se encuentra en los límites entre estas dos últimas, probablemente porque esta región fue un refugio climático durante el Pleistoceno.